Perancangan dan Analisis Pembangkit Listrik Tenaga Surya di Gedung Fakultas Teknik UKI Toraja - Kurniawan, Reskyel; Pineng, Martina; Pawarangan, Ishak (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
Solar energy is one of the alternative energy sources to produce electrical energy which is included in renewable energy and is environmentally friendly with low pollution levels. The PLTS system is one of the generating systems that utilise sunlight energy to produce electrical energy and has the potential to be developed in Indonesia. In this research, the design and analysis of the PLTS system in the UKI Toraja Faculty of Engineering building whose electrical energy supply still depends entirely on PLN. The solar modules needed are 92 panels with a capacity of 200 Wp each panel, and the inverter used is 1 piece with a capacity of 1000V. Economic analysis which includes the value of the parameter needs in the Faculty of Engineering building of the Universitas Kristen Indonesia Toraja with an initial investment of Rp.290,910,000, maintenance and operational costs of Rp.2,909,100, life cycle costs of Rp.315,409,567.47, and annual cash inflows of Rp.37,479,568.75, investment feasibility analysis which includes a net present value of Rp.346,199.22, a profitability index of 1.00119, a discounted payback period of 8 years and 5 months, and an internal rate of return of 11.020%.